Some Issues in Implementing Forest Carbon Sink Projects to Realize Carbon Emission Reduction for Climate Change Mitigation - Shengrong Zhang; Qi Zhang; Shengdong Zhu (BioResources, 2023)
The global climate warming caused by greenhouse gases poses a great threat to human living and biological ecosystems. To mitigate climate change, many measures have been taken to reduce carbon dioxide emissions. Among them, the forest carbon sink (FCS) is considered as one of the most economical and effective carbon sequestration methods to realize carbon emission reductions in next 30 to 50 years. FCS projects are being implemented in many countries to increase their carbon sequestration and thereby to realize carbon emission reductions. However, there are some issues associated with implementation with such policies. Firstly, these projects mainly have focused only on carbon sequestration and have ignored the comprehensive ecological effects to obtain their best economical benefits. Secondly, implementing these projects fails to establish a sustainable and healthy forest industry because they place too much reliance on preferential policies from governments. Finally, the projects lack systematic technological standards and legislation to guarantee their smooth implementation. This editorial briefly discusses these issues for the suitable implementation of the FCS projects.